Code-Switching Phenomena In Online Communication (Case Study) At Politeknik Unggul LP3M Medan (6th Semester Students AP6A) - Cici Handayani (Jurnal Warta Dharmawangsa, 2026)
This study aims to analyze the phenomenon of code-switching in online communication among students of Politeknik Unggul LP3M, especially students from the AP6A major class. The study employed a quantitative descriptive research design involving 15 students as respondents selected using purposive sampling techniques. Data were collected through questionnaires distributed via Google Forms using a five-point Likert scale and supported by documentation of online communication activities. The research variables consisted of Code-Switching Behavior as the independent variable and Online Communication Effectiveness as the dependent variable. The data were analyzed using descriptive statistics and simple linear regression analysis with the assistance of IBM SPSS Statistics version 26. The results showed that students frequently used code-switching in online communication activities through platforms such as WhatsApp, Instagram, Telegram, and TikTok. The regression analysis indicated that code-switching behavior significantly influenced online communication effectiveness with a significance value of 0.001 (<0.05) and an R² value of 0.645. The findings reveal that code-switching helps students communicate more confidently, efficiently, and flexibly in digital interaction. However, excessive use of mixed-language communication may reduce formal language accuracy. Therefore, balanced bilingual communication practices are necessary in academic and social contexts.